PENGGUNAAN METODE PEMBELAJARAN KOOPERATIF TIPE JIGSAW UNTUK MENINGKATKAN MINAT BELAJAR IPS SISWA KELAS VIII.1 SMP NEGERI 1 RANTAU KOPAR KABUPATEN ROKAN HILIR - Selfianora Hafrida; Sri Kartikowati; Hardisem Syabrus Syabrus (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstrack:Sstudy interest is very important in the learning process since it can lead students to have a concentration. However, the learning process of IPS has problemsdue to lack of students interest. The purpose of this study is to increase study interest in learning by applying the model of Jigsaw. The subjects students of SMPN 1 Rantau Kopar at clan of VIII academic year 2015/2016 totally 22 students encompases 11 male students and 11 famale students. Data obtainet using observation techniques. Data analysis technique used is descriptive statistics on tables and graphs. The result of this reserch in that the teacher’s success in implementing Jigsaw teacher’s increase students interest in the learning process that indicated by an incrase of study interest from rose to 96 in the second cycle.Keywords: Methode Cooperative Learning Jigsaw, student Interest .